Oxycodone/naloxone prolonged‐release tablets in patients with moderate‐to‐severe, chronic cancer pain: Challenges in the context of hepatic impairment. Issue 1 (3rd March 2021) - Le, Brian H; Aggarwal, Ghauri; Douglas, Carol; Green, Michael; Nicoll, Amanda; Ahmedzai, Sam
Abstract: Opioids such as oxycodone are recommended in the management of moderate‐to‐severe, chronic cancer pain. All opioids can potentially cause constipation, which may be a significant barrier to their use. Multiple randomised clinical trials have shown that the use of naloxone as a peripherally acting mu‐opioid receptor antagonist, in combination with oxycodone can prevent or reduce opioid‐induced constipation while having equivalent analgesic efficacy to oxycodone alone. However, clinical experience has shown that unexpected events may occur in some patients when unrecognized liver impairment is present. We describe the underlying biological reasons and propose simple, but effective steps to avoid this unusual but potentially serious occurrence. In healthy individuals, naloxone undergoes extensive hepatic first pass metabolism resulting in low systemic bioavailability. However, in patients with hepatic impairment, porto‐systemic shunting can increase systemic bioavailability of naloxone, potentially compromising the analgesic efficacy of oral naloxone–oxycodone combinations. This reduced first pass effect can occur in a range of settings that may not always be apparent to the treating clinician, including silent cirrhosis, non‐cirrhotic portal hypertension and disruption of liver internal vasculature by metastases. Hepatic function test results correlate poorly with presence and extent of liver disease, and are not indicative of porto‐systemic shunting. Presence of hepatic impairment should thus be considered when medication‐related outcomes with oxycodone–naloxone combination are not as expected, even if liver function test results are normal.